2020
DOI: 10.3390/biom10091329
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Tyrosine Kinase TrkA Is Increased and Targetable in HER2-Positive Breast Cancer

Abstract: The tyrosine kinase receptor A (NTRK1/TrkA) is increasingly regarded as a therapeutic target in oncology. In breast cancer, TrkA contributes to metastasis but the clinicopathological significance remains unclear. In this study, TrkA expression was assessed via immunohistochemistry of 158 invasive ductal carcinomas (IDC), 158 invasive lobular carcinomas (ILC) and 50 ductal carcinomas in situ (DCIS). TrkA was expressed in cancer epithelial and myoepithelial cells, with higher levels of TrkA positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…Although amplification of the NTRK1 gene does not always lead to mRNA over-expression, TrkA protein is expressed in many breast cancers and thus can be a therapeutic target. In contrast to our results, another study that examined expression of TrkA at the protein level suggested that the receptor is more often expressed in HER2 positive cancers compared to luminal and basal carcinomas[ 64 ]. This study also confirmed discrepancies between gene dosage and protein expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Although amplification of the NTRK1 gene does not always lead to mRNA over-expression, TrkA protein is expressed in many breast cancers and thus can be a therapeutic target. In contrast to our results, another study that examined expression of TrkA at the protein level suggested that the receptor is more often expressed in HER2 positive cancers compared to luminal and basal carcinomas[ 64 ]. This study also confirmed discrepancies between gene dosage and protein expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Since we demonstrated that blocking NGF action, and specifically TRKA signaling, impairs OPC survival and differentiation, we hypothesized that also the protection from OGD-induced cell death may occur through this receptor. In fact, TRKA activation by NGF protects cultured neurons from glucose levels fluctuation by activating the AKT pathway ( Yan et al, 2020 ), a signal transduction path which is activated by NGF in different cell types ( Geetha et al, 2013 ; Griffin et al, 2020 ). In these contexts, NGF seems to exert its action, by TRKA interaction, increasing the presence of the phosphorylated form of AKT in the nucleus ( Xuan Nguyen et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that TrkA overexpression enhances BC cell growth and invasion by activating Erk1/2 and PI3K-AKT-mediated signaling pathways ( 54 ). Functional experiments have demonstrated that TrkA inhibitor reduces cell viability by decreasing phosphorylated TrkA and downstream AKT, providing therapy for HER2-positive BC ( 55 ). For those drugs that have not yet been applied in the clinic, our study provides some theoretical basis for their development.…”
Section: Discussionmentioning
confidence: 99%